"Mist Polymerization" Method for Fabricating Superhydrophobic Cotton Fabrics. Issue 1 (March 2020) - Liu, Xiangdong; Li, Lin
Abstract: Recently, our group developed a surface modification technology using "mist polymerization" to fabricate functional cotton fabrics. The "mist polymerization" method have both the advantages of liquid-phase and gas-phase reactions: less damages on the structure of the matrix material, very fine and controllable layer, wide applicable monomer range, and small monomer dosage. Here, I summarize recent works on the application of the "mist polymerization" method to fabricate superhydrophobic fabrics.